Adsorption of Copper on Iridium - Hashim, K. (Libyan Journal of Science &Technology, 2022)
The work described in this paper is a study of copper adsorption on the whole tip surface of iridium field emitter. The study has been carried out using Field Emission Microscope. Changes in electron work function (Φ) of the iridium substrate, which are produced by vapour deposition of submonolayer of copper in Ultra High Vacuum (UHV), have been measured by noting the changes in the slope of Fowler-Nordheim (FN) plots.